The reality of using virtual laboratories in teaching natural sciences for secondary school teachers in the Jazan Education Department - Kariri, Aisha Yahya Ahmed; Faqihi, Ahmed Yahya (Journal of Curriculum and Teaching Methodology, 2022)
The research aimed to identify the reality of the use of virtual laboratories in teaching natural sciences among secondary school teachers in the Jazan Education Department from their point of view, and its relationship to gender and number of years of experience, and the research’s use of the descriptive survey method; The research sample consisted of a random sample of (216) male and female teachers of natural sciences in the secondary stage, and a questionnaire consisting of (32) items was applied to them, distributed on three axes. The study concluded that the level of virtual laboratories availability in secondary schools in Jazan region came The degree of natural science teachers’ use of virtual lab technology in science teaching at the secondary level came to a medium degree, while the obstacles to using virtual labs in teaching natural science came to a large degree, and the results concluded that there were no statistically significant differences about the reality of using virtual labs in Teaching natural sciences among secondary school teachers is due to the variable of sex, while there are statistically significant differences about the reality of using virtual laboratories due to the variable number of years of experience in favor of those with experience from 1 to 5 years compared to other groups in my axes: the level of availability of virtual laboratories in secondary schools in Jazan region , and the degree to which science teachers use virtual laboratories in teaching natural sciences at the secondary level, while the differences are in favor of the experienced from 11-15 years, and more than 15 years compared to other groups in the axis of obstacles to the use of virtual laboratories in teaching natural sciences at the secondary stage in the Jazan region, and in the total score of the questionnaire. The research recommended the need to  pay attention to intensifying training courses for science teachers, especially those with higher experience, to train them on the use of virtual laboratories in teaching natural sciences.
Keywords: Virtual labs; natural sciences